The factors affecting auditor switching in manufacturing companies listed in Indonesia Stock Exchange (BEI) - Istainul Khasanah; Joicenda Nahumury (Universitas Hayam Wuruk Perbanas, 2013)
This study aims to empirically prove the effect of the audit opinion, change in management,public accountant firm’s size, the percentage change in ROA, financial distressand the growth of corporate on auditor switching. The samples in this study aremanufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2006-2011.There were 492 companies collected for observations in which they were taken by themethod of purposive sampling. An analytical technique employed is logistic regressionanalysis. During the six years of research, descriptive statistics indicate that only 55or 11.25% of the observed companies have changed their auditor, and the rest 437companies or 88.75% did not perform auditor switching. It was found that only publicaccountant office size that affects the auditor switching among six variables studied.The other five independent variables have no impact at all. This study has proved thatcompanies which hired the public accountant firms affiliated with the big four chooseto stay afloat using them, because in fact, the public accountant firms affiliated withthe big four are considered having a higher quality to conduct the audit on financialreports of go public companies.